Pomegranate marketing: Traditional skills for the future - Paños Callado C. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
The international trade of pomegranates produced in Spain and exported to Europe and other countries around the world is studied from 1986, year in which Spain joined the present European Union, to 1998. This study attempts to define the main issues of Spanish pomegranate exportation and to identify the basic elements of the Spanish export sector. In the light of such issues, options are indicated to enable the pomegranate trade to respond in the future to the increase in production.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)